¿Emisiones a la atmósfera?, ¿por qué no mejor de bonos verdes? (2021)
Used by public and private institutions, green bonds are part of a debt securities market, that is, in which financing is presented through the issuance of said bonds. They are also known as fixed-income securities, since between issuers and buyers the amount of money that will be obtained and the fixed interest are known exactly. The definition of what they are is in the international study The potential of green bond markets in Latin America and the Caribbean, financed by the EU-LAC Foundation and in which academics from EAFIT, the firm Hill and Get2C participated.